Tourist preferences for Balinese local food: Price, authentic recipes, and restaurant service systems in Bali - I Wayan Pugra; I Wayan Mudana; Ni Wayan Wahyu Astuti (YAYASAN MITRA PERSADA NUSANTARA, 2026)
This study investigates how tourists prioritize price, authenticity of recipes, and restaurant service systems when consuming Balinese local food. Drawing on attributes commonly used to assess culinary tourism choices—price, food quality, service systems, and cooking methods —the research aims to compare domestic and foreign tourists’ preferences across different restaurant types in Bali. A quantitative survey using purposive sampling will target at least 320 tourists (balanced domestic and international), adapting attribute scales from prior studies on Balinese culinary tourism and food consumption value. Data will be analysed using descriptive statistics and multinomial logistic regression to identify how price sensitivity, preference for authentic versus innovative recipes, and preferred service formats (counter service, self-service, or table service) vary by origin, age, and travel motivation. The study is expected to confirm that domestic tourists emphasize affordable, authentic dishes and convenient service, while foreign tourists value consistent pricing, authenticity, and acceptable hygiene standards in service environments. Findings will provide practical guidance for restaurant managers and destination marketers to segment menus, pricing, and service concepts that better match key tourist segments in Bali’s culinary tourism market.